La representación del cuerpo queer en el teatro latinoamericano - Foster, David William (Latin American Theatre Review, 2004)
Four works of Latin American/Chicano theatre are examined in terms of their construction of the queer body: Nelson Ro drigues’s O beijo no asfalto; Luis Alfaro’s "Cuerpo politiza di"; Virgilio Piñera’s Una caja de zapatos vacía; and Copi’s Eva Perón. Of interest is the demonstration of how social ideologies of sexuality, particularly homophobia, mean that it cannot be a question of works of cultural production simply "representing" the queer body, but rather of "creating" it as part of a particular structure of sexual semiotics. (DWF)